2014
DOI: 10.1093/glycob/cwu080
|View full text |Cite
|
Sign up to set email alerts
|

RNAi screening of human glycogene orthologs in the nematode Caenorhabditis elegans and the construction of the C. elegans glycogene database

Abstract: In this study, we selected 181 nematode glycogenes that are orthologous to human glycogenes and examined their RNAi phenotypes. The results are deposited in the Caenorhabditis elegans Glycogene Database (CGGDB) at AIST, Tsukuba, Japan. The most prominent RNAi phenotypes observed are disruptions of cell cycle progression in germline mitosis/meiosis and in early embryonic cell mitosis. Along with the previously reported roles of chondroitin proteoglycans, glycosphingolipids and GPI-anchored proteins in cell cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 65 publications
1
11
1
Order By: Relevance
“…In previous studies by Struwe et al (Struwe et al 2009;Struwe and Warren 2010), tunicamycin, a widely used inhibitor of DPAGT1, was used to study functions of N-glycans in C. elegans. As discussed in our paper (Akiyoshi et al 2015), slightly different phenotypes were observed between algn-7 RNAi-treated worms and tunicamycin-treated worms. In studies using other organisms, it was shown that tunicamycin affects various biochemical processes (Reiling et al 2011) including glucose transport (Rojas et al 2014), glycosphingolipid synthesis (Yusuf et al 1983), and innate immunity without affecting N-glycosylation and ER-stress pathways (Kim et al 2013).…”
Section: Introductionsupporting
confidence: 62%
See 2 more Smart Citations
“…In previous studies by Struwe et al (Struwe et al 2009;Struwe and Warren 2010), tunicamycin, a widely used inhibitor of DPAGT1, was used to study functions of N-glycans in C. elegans. As discussed in our paper (Akiyoshi et al 2015), slightly different phenotypes were observed between algn-7 RNAi-treated worms and tunicamycin-treated worms. In studies using other organisms, it was shown that tunicamycin affects various biochemical processes (Reiling et al 2011) including glucose transport (Rojas et al 2014), glycosphingolipid synthesis (Yusuf et al 1983), and innate immunity without affecting N-glycosylation and ER-stress pathways (Kim et al 2013).…”
Section: Introductionsupporting
confidence: 62%
“…We have been studying C. elegans glycogenes which are human glycogene orthologues, and the results of our research are summarized in our C. elegans Glycogene Database (CGGDB). In the paper describing the database (Akiyoshi et al 2015), we reported that inhibition of N-glycosylation pathway genes results in an ER stress response as judged by increased expression of the GFP-tagged hsp-4 (C. elegans BiP/HSP70 orthologue) transgene. Increased expression was observed in the following RNAi-treated animals: algn-7, algn-13, algn-14, algn-2 and algn-11 (these are cytoplasmic alg genes which are possible ALG gene orthologues in the nematode) and ostb-1, dad-1 and stt-3 (these are genes coding subunits of the oligosaccharyltransferase complex).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…XBP-1-mediated UPR ER is a critical factor for immunity against PA14 ( Fig 6A) [29,31,39]. Similar to XBP-1 and UPR ER , OST-regulated N-glycosylation is crucial for ER protein homeostasis ( Fig 3A-3H) [3,57], and we showed that the OST contributes to protection against PA14 infection. Interestingly, our transcriptomic data indicate that PA14 infection down-regulated many abu genes (abu-1, 6, 7, 9, 10, and 15) and pqn genes (pqn-2, 37, 57, 60, 63, and 74), which were suppressed by the inhibition of OST (S5 Table).…”
Section: Ost May Contribute To Pmk-1-dependent Immunity Via Maintainimentioning
confidence: 60%
“…CAZy stores information on several hundred thousands of enzymes,b ut less than 5% of them have experimentally established activities.T he major drawback of CAZy is the absence of synthesized carbohydrate structures and bibliographic references to original research. Among the dedicated databases,t here are ECODAB (data on E. coli glycosyltransferases (GTs)); [14] Rice GT Database (data on rice GTs); [18] GlycoGene Database (GGDB) and Caenorhabditis elegans GlycoGene Database (data on CAZyrelated genes in human and C. elegans,r espectively); [19] CSDB GT (CSDB subdatabase,w hich currently provides experimentally confirmed and predicted GT activities for E. coli and Arabidopsis thaliana); [20] and some others. [21] Glycoinformatics Projects Are Isolated Islands in the Sea of Data Information support for glycomics is falling behind that for genomics and proteomics,a nd glycoscientists have al imited access to both the global data on natural carbohydrates and tools of their processing.…”
Section: Structural Databases Are the Foundation Of Glycoinformaticsmentioning
confidence: 99%